Topical gel preparation from Staphylococcus epidermidis isolate extract accelerated healing on incision wound model in rats - Mochtar, Chaerul Fadly; Bakhtiar, Muh Irham; Hamzah, Hasyrul; Pratama, Aldo; Rasyidah, Jamiatur; Indriyani, Juniar Rakhmatia; Alfiannur, Muhammad Rizky; Amalia, Nadhifah Suci; Putri, Nur Octaviany; Damis, Nur Lutfiah (Indonesian Journal of Pharmacology and Therapy, 2024)
A wound is a disorder of skin integrity caused by physical trauma or disease. Wound healing is a natural restorative response to tissue injury. It is a complex dynamic physiological process involving several overlapping phases. Although wound management has been applied, however, some time it is associated withmajor drawbak including invasiveness, antibiotic resistance, and high costs. Natural medicines are being developed for wound management to resolve the drawback. Commensal Staphylococcus epidermidis was proven to play a role in natural wound healing process. This study aimed to investigate the wound healingactivity of a topical gel preparation containing S. epidermidis isolate extract on an incision wound model in rats. The methanol extract of S. epidermidis isolate was prepared by maceration and used as an active ingredient of the topical gel using NaCMC as a gelling agent. A physical stability test was carried out by assessingorganoleptic properties, pH value, homogeneity, dispersion, and viscosity of the gel preparation. The gel preparation was then topically applied once-daily for 11 d on incision wound model of male white rats (Rattus norvegicus). The wound healing was observed daily and calculated using Morton’s formula. Nosignificant change in the physical stability parameters of the gel preparation was observed during observation on day 1, 7, and 14 (p>0.05). A significant increase in wound healing after the application of the gel preparation compared to negative control was observed (p<0.05). In contrast, no significant difference inwound healing between the gel preparation and the positive control group was observed (p>0.05). In conclusion, the topical gel preparation from S. epidermidis isolate extract accelerates healing on incision wound models in rats.